Vasopressin and angiotensin receptors of the medial septal area of the brain in the control of thirst and salt appetite induced by vasopressin in water-deprived and sodium-depleted rats - Pavan de Arruda Camargo, Gabriela Maria; de Arruda Camargo, Luiz Antonio; Saad, Wilson Abrao (Elsevier B.V., 2007)
In this study we investigated the influence of d(CH2)(5)-Tyr (Me)-AVP (A(1) AVP) and [Adamanteanacatyl(1),D-ET-D-Tyr(2), Va1(4), aminobutyril(6) ,As-8,As-9]-AVP 9 (A(2)AVP), antagonists of V-1 and V-2 arginine(8)-vasopressin (AVP) receptors, respectively, as well as the effects of losartan and CGP42112A, antagonists of angiotensin II (ANGII) AT(1) and AT(2), receptors, respectively, on water and 0.3 M sodium intake induced by water deprivation or sodium depletion (furosemide treatment) and enhanced by AVP injected into the medial septal area (N4SA). A stainless steel carmulawas implanted into the medial septal area (NISA) of male Holtzman rats AVP injection enhanced water and sodium intake in a dose-dependent manner. Pretreatment with V-1 antagonist injected into the MSA produced a dose-dependent reduction, whereas prior injection of V-2 antagonist increased, in a dose-dependent manner, the water and sodium responses elicited by the administration of AVP. Both AT(1) and AT(2) antagonists administered into the MSA elicited a concentration-dependent decrease in water and sodium intake induced by AVP, while simultaneous injection of the two antagonists was more effective in decreasing AVP responses. These results also indicate that the increase in water and sodium intake induced by AvT was mediated primarily by MSA AT(1) receptors. (c) 2007 Published by Elsevier B.V.
Keywords: arginine vasopressin; vasopressin V-1 antagonist; vasopressin V-2 antagonist; angiotensin AT(1) antagonist; angiotensin AT(2) antagonist; water intake; sodium intake; medial septal area